The effects of alternative forced-molting methods on the performance and egg quality of commercial layers - Molino, AB [UNESP] (2009)
This study aimed at studying alternative methods to induce molting and to compare them with the conventional forced-molting method (fasting). In the experiment, 420 70-week-old layers were used. The total experimental period was 140 days. Molting was induced during the first 28 days, when birds were submitted to the experimental treatments, and bird performance and egg quality parameters were determined during 112 subsequent days. A completely randomized experimental design was applied in a 5x2 factorial arrangement of five feed restriction regimes (0, 15, 30, 45, or 60g feed/bird/day) and with or without the addition of coarse-particle limestone to the feed, with seven replicates of six birds each. Egg quality was evaluated at the end of each 28-day period for three consecutive days, using three eggs per experimental unit (21 eggs/treatment), with a total of 210 eggs. It was concluded that feeding 15g feed/bird/day to induce molting is feasible, as birds submitted to this treatment presented similar performance and better egg quality than those submitted to fasting during molting. The use of coarse-particle limestone during molting did not influence post-molting bird performance or egg quality.